Comparison of mixed enzymatic pretreatment and post-treatment for enhancing the cellulose nanofibrillation efficiency. (December 2019) - Bian, Huiyang; Dong, Maolin; Chen, Lidong; Zhou, Xuelian; Ni, Shuzhen; Fang, Guigan; Dai, Hongqi
Highlights: Mixed enzymatic pretreatment and post-treatment were compared to produce LCNF. Enzymatic pretreatment was more suitable to facilitate cellulose nanofibrillation. The number-average height of fibril became smaller as the enzyme dosage increased. The entire process was environmentally friendly without changing crystal structure. This work gives us insights into more efficient and reasonable enzymatic treatment. Abstract: In this work, lignocellulosic nanofibrils (LCNF) produced from mechanical fibrillation with mixed enzymatic pretreatment or post-treatment were compared and the chemical composition, water retention value (WRV), average-number height and crystallinity for the obtained LCNF were evaluated. Compared to pure mechanical fibrillation, both mixed enzymatic pretreatment and post-treatment could efficiently facilitate cellulose nanofibrillation. Moreover, mixed enzymatic pretreatment was more suitable for LCNF production, resulting in a relatively higher WRV of 909% and smaller average-number height of 15 nm. These discoveries provide new insights into a more efficient biological method for the production and application of cellulose nanomaterials.